سلطة الإدارة في توقيع الجزاءات الإدارية في النظام القانوني الجزائري - سناء همايسية (My University, 2020)
SUMMARY NOTE: Giving lawmakers the administration the power to impose administrative sanctions is one of the most effective and necessary ways to control and regulate the actions and activities of individuals and deter violators of laws and regulations. In view of the seriousness of this measure, a number of safeguards have been put in place to protect individuals' rights and freedoms from the use of this authority by the administration, which may lead to its arbitrariness, They, in turn, constrain management to respect the principle of legality while making decisions containing administrative sanctions. ,,,,,,,,,,,,,,,,,,,,,,,,, ملــــــــــــــــــــــــــــــخص المذكــــــــــــــــــــــــــــرة: إن منح المشرع الإدارة سلطة توقيع الجزاءات الإدارية يعد من السبل الناجعة و الضرورية التي تهدف إلى ضبط و تنظيم الأعمال و الأنشطة التي يقوم بها الأفراد و ردع المخالفين للقوانين و اللوائح،و بالنظر لخطورة هذا الإجراء فقد أحيط بجملة من الضمانات التي تضمن الحماية لحقوق و حريات الأفراد من إستعمال الإدارة لهذه السلطة و الذي قد يؤدي إلى تعسفها،و هي بدورها قيد على الإدارة لإحترام مبدأ المشروعية أثناء إصدارها للقرارات المتضمنة الجزاءات الإدارية. ,,,,,,,,,,,,,,,,,,,,,,,,,, NOTE DE SYNTHÈSE : Donner aux législateurs le pouvoir d’imposer des sanctions administratives est l’un des moyens les plus efficaces et nécessaires pour contrôler et réglementer les actions et les activités des individus et dissuader les contrevenants aux lois et aux règlements. Compte tenu de la gravité de cette mesure, un certain nombre de garanties ont été mises en place pour protéger les droits et libertés des personnes contre l’utilisation de ce pouvoir par l’administration, ce qui peut entraîner son arbitraire, Ils contraignent à leur tour la direction à respecter le principe de légalité tout en prenant des décisions comportant des sanctions administratives.